A translated town? Translation in the linguistic landscape along the US border with Mexico - González Núñez, Gabriel (Meta, 2024)
Cities are the hubs of the modern world and, in border towns between states where different languages are used, these hubs are bilingual. Such bilingual towns offer opportunities to examine the extent to which translation, including the decision not to translate, plays a role in shaping the public spaces of cities. This article seeks to do so by reporting on a linguistic landscape study carried out in Brownsville, a city that sits on the Texas border with Mexico. The study will survey two streets in Brownsville with a special concern for both untranslated and translated signs as a way of thinking about what the presence of each type of sign indicates. The study’s findings highlight the role of both non-translation and translation in creating a public space that may (or may not) be inclusive of the local population. From there, some conclusions can be drawn about the significance of translation in the linguistic landscape, and its implications for public policy, particularly among bilingual populations.